PERSEPSI PEDAGANG TENTANG KONDISI PASAR RAYA TIMUR DI KOTA PADANG - Ateng, Ateng; Rianto, Slamet; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
Â This research aims to get information about traders perceptions about the condition of cleanliness, orderliness and comfort conditions at Pasar Raya in East Padang.Type of this research was descriptive research and population of this research was 2.465 traders in Pasar Raya East Padang. Samples were taken with a random sampling proportionate technique to the proportion of 5 % of the total population that is numbered 123 respondents.The results of this research showed that according to the traders : 1) hygiene condition in Pasar Raya East Padang classified in the category quite well. It is based on the level of attainment of respondents (TCR) was 69.2 %, because the market is not so clean and seen the garbage strewn and muddy, 2) order condition Pasar Raya East Padang classified in the category quite well. It is based on the level of attainment of respondents (TCR) was 70.7 %, because in this market it still looks the irregular parking of vehicles and street vendors hawking wares through the boundary line has been determined and unruly, and 3) Comfort conditions of East Raya Markets in Padang classified in the category quite well. It is based on the level of attainment of respondents (TCR) was 74.2 %, because in this market most traders said that there are many street pickpockets and robbers, so merchants and shoppers feel comfort disturbed.